Mallampati score and intubation succes in neurosurgery patients - Yusuf, Hanafi; Donsu, Jenita Doli Tine; Maryana, Maryana; Herawati, Lucky (JHeS (Journal of Health Studies), 2024)
Surgical procedures involving the nervous system have an incidence of intubation failure in all age categories and cause severe complications such as hypoxia, aspiration, and increased intracranial pressure, which can worsen the patient's neurological condition. Accurate preoperative assessment is important to predict intubation-related complications. One of the important predictors of intubation success is the Mallampati score. Several studies on Mallampati Score showed different results, so this study aimed to find out the relationship between Mallampati score and intubation success in neurosurgery patients. This study is an observational analysis with a cross-sectional design, conducted from February 12 to March 23, 2024. The sampling technique used a total sampling with 33 respondents. Data analysis was carried out using the Chi-Square test. Most respondents with Mallampati Score 1-2 successfully underwent intubation (42.4%). Respondents with Mallampati scores in grades 3-4 mostly experienced failed intubation (39.4%). There was a statistically significant association between Mallampati scores and intubation success in neurosurgical patients. The Mallampati score can be used as part of a comprehensive airway assessment. Additional instruments and comprehensive clinical evaluation improve the success of intubation and reduce the risk of complications. Respondents with Mallampati scores in grades 3-4 mostly experienced failed intubation (39.4. Additional instruments and comprehensive clinical evaluation can improve the success of intubation and reduce the risk of complications. Future research is encouraged to study how cultural and demographic factors affect Mallampati's score and its predictive value in different populations, which could provide insights into its generalization and application in various healthcare contexts.